Economic evaluation of improved vertisol drainage for food crop production in the Ethiopian highlands - Asamenew, G.; Jutzi, S.C.; Tedla, A.; McIntire, John M. (International Livestock Centre for Africa, 1988)
Outlines an economic evaluation of an improved surface drainage technology, using the broad-bed-maker (BBM) on-farm in four different vertisol areas of the Ethiopian highlands. Presents data on crops and number of areas covered for the on-farm drainage technology, on cost structure of the BBM, and on human and oxen labour input in traditional seed covering and the construction of the BBM.